Comparação do método simplificado e de vento sintético para consideração de forças laterais em edifícios de concreto armado - Batista, Juliano Lisboa Cezar Marques (2022)
Currently, because of urbanization, the verticalization of buildings is becoming increasingly present, as this resource allows better use of space, which is highly valued in large centers. The gain in height of these buildings implies the advancement of studies directed to structures, considering that slender buildings are more vulnerable to dynamic requests. One of the main factors responsible for the lateral efforts in tall buildings is the action of the wind, however, the behavior and intensity of the gusts is unpredictable, providing a high level of uncertainty, where researchers face the challenge of developing models and techniques to achieve the maximum precision in the calculations of these requests. This work aims to compare the Simplified Method NBR 6123 (ABNT, 1988) and the Synthetic Wind Method (Franco, 1993) in reinforced concrete buildings with multiple floors, using the shear building model to represent the structures and the MATLAB software for the implementation of the computational code. The method pointed out by Franco (1993) considers the loading of wind gusts as dynamic, varying according to time and height, different from that offered by NBR 6123 (ABNT, 1988). To carry out the study, three models of buildings were used, different from each other in structural composition and number of floors, Model I have 8 floors and a total height of 24 meters, Model II is a building with 20 floors, with a total height of 60 meters containing a rigid core and for Model III, 30 floors with a total height of 90 meters. It was found that the results (lateral forces and maximum displacements) obtained by the Simplified Method were, in all cases, lower than those found by the Synthetic Wind Method, which indicates that the dynamic analysis method presents results in favor of safety.